Capacity Building Kader Pemberdayaan Masyarakat Desa (KPMD) Melalui Pelatihan Public Speaking Desa Sukahurip Kecamatan Cihaurbeti - Sapitri, Dewi; Inggris, Raja; Hayat, Dila Fadlilah; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The problem found was that the potential for utilizing the performance of cadres in Palasari Hamlet, Sukahurip Dirasi Village had not been optimally empowered, due to a problem that had not been resolved. So, to solve  this problem, it’s necessary to take action to build capacity for village community empowerment cadres through public speaking training in an effort to improve the quality of human resources in Palasari hamlet. This  research uses descriptive qualitative techniques. This research uses primary data which reflects that information continues to develop in responding to challenges in the field. This aims to provide an overview and increase knowledge about public speaking so that cadres expected to be able to implement the learning that has been delivered, and the welfare of the people of Sukahurip village, especially Palasari hamlet, has increased.